Constructing university-based teacher educators: serendipity, complexity and community. Issue 3 (3rd April 2023) - Barrow, Mark; Xu, Linlin
ABSTRACT: While previous studies have explored many aspects of teacher educators' identities, limited attention has been paid to how teacher educators understand the process of their academic identity construction in higher education. To address this issue, we draw on interviews and other supplementary data collected from 19 teacher education academics in two New Zealand universities. To bring the participants' voices to the fore, we analyse the interview data thematically. The findings show that the participants conceptualise the process of academic identity construction across two interrelated dimensions. They perceive it as a development of professional identity, practice and as a learning journey that is entangled with contestation, reflection, and negotiation with multiple but conflicting forces from professional school teaching and academic spaces. We conclude by suggesting that academic identity construction is a non-linear and unfinished process. It involves the teacher educators continuously moving back and forth between different communities, with constant reflection, negotiation and renewing of identities in response to dynamic, complex socio-cultural contexts.